Current Topics in Microbiology and Immunology
DOI: 10.1007/3-540-26397-7_1
|View full text |Cite
|
Sign up to set email alerts
|

What Is a Quasispecies?

Abstract: The concept of the quasispecies as a society formed from a clone of an asexually reproducing organism is reviewed. A broad spectrum of mutants is generated that compete one with another. Eventually a steady state is formed where each mutant type is represented according to its fitness and its formation by mutation. This quasispecies has a defined wild type sequence, which is the weighted average of all genotypes present. The quasispecies concept has been shown to affect the pathway of evolution and has been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
1

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 117 publications
3
133
0
1
Order By: Relevance
“…Potentially, multiple strains exist in a cloned homogenate prior to transmission out of which one strain can become the dominant species depending on selection for the strain most congruent with the host PrP molecule. This interpretation is analogous to the quasispecies theory of RNA viruses (Biebricher and Eigen, 2006). Alternatively, new strains might be generated de novo due to strain "mutations" of unknown etiology (Weissmann, 1991).…”
Section: Prion Strainsmentioning
confidence: 76%
“…Potentially, multiple strains exist in a cloned homogenate prior to transmission out of which one strain can become the dominant species depending on selection for the strain most congruent with the host PrP molecule. This interpretation is analogous to the quasispecies theory of RNA viruses (Biebricher and Eigen, 2006). Alternatively, new strains might be generated de novo due to strain "mutations" of unknown etiology (Weissmann, 1991).…”
Section: Prion Strainsmentioning
confidence: 76%
“…The data showed that this was not the case and that a set of quasispecies was present from the beginning of the outbreak. Quasispecies can be described as a population of viruses without a defined unique sequence structure, but rather as a weighted average of a large number of different individual sequences (Biebricher & Eigen, 2006;Domingo et al, 1978). Quasispecies a i , a ii and a iii were all present at Troughend, Oakhill and Daktari farms at the beginning of the a clade outbreak and within 3 days of each other.…”
Section: Ahs Outbreak Western Cape 2004mentioning
confidence: 99%
“…Because several of the criteria suggested by the ICTV for the definition of viral species (e.g., morphological characteristics, protein features and antigenic properties of members) are not applicable to viroids, a fundamental question arises: why does Section 3.32 of the International [2,6]. Finally, also resembling viruses, mutation and recombination during replication have been identified as the major mechanisms driving evolution and adaptation of viroids to hosts or environmental constraints (reviewed by [16]).…”
Section: Current Viroid Taxonomy Schemementioning
confidence: 99%